New Spectrophotometric Estimation Of Gatifloxacin In The Tablets Using Mixed Solvency Approach - NEHA BHAWSAR; RAJESH KUMAR MAHESHWARI; AASIF ANSARI; YASHWARDHAN SAKTAWAT (International Journal of Pharma and Bio Sciences, 2011)
On the basis of a large number of solubilization experiments on poorly water-soluble drugs, the author is of the opinion that hydrotropy is another type of co-solvency and all water soluble substances whether liquids or solids may act as solubilizers for poorly water-soluble drugs. In the present investigation, mixed-solvency concept has been utilized for solubility enhancement of poorly water-soluble drug, gatifloxacin. One blend containing mixed solvent system of sodium citrate, sodium benzoate, glycerin and PEG-4000 (ten percent each) was made to study the influence on solubility of gatifloxacin. The blend was found to increase the solubility of gatifloxacin synergistically. This concept shall prove a boon in pharmaceutical field (and also in non-pharmaceutical field viz. chemical engineering etc.). In the present investigation, the mixed-solvency concept has been employed to analyze gatifloxacin in the bulk drug sample precluding the use of organic solvents (a way towards green chemistry).